Replacement of congenitally missing maxillary lateral incisor with ipsilateral canine: A case report - abdullah Alnazeh (KARACHI MEDICAL AND DENTAL COLLEGE, 2020)
Abstract Congenital missing lateral incisor of maxilla is a common tooth anomaly. Its replacement can have many options. The choice ought to be understandable for patients or guardians hence effectively address the patient's issues. Regardless of canine replacement, solitary inserts, tooth-supported prosthesis are techniques for patients with missing maxillary missing lateral incisors, although numerous confront are engaged with acquiring and holding ideal outcomes. In this case, report a case of 16 year old boy was discussed which has the diagnosis of Class II division 1 with missing upper laterals and anterior open bite. Plan was  to perform space closure by canine lateralization and retraction of upper anterior to reduce the overjet followed by extraction of lower 5s to alleviate anterior crowding, correct molar relationship, maintain lower anterior teeth position, finishing, and alignment followed by retention.